2016
DOI: 10.1039/c6mt00003g
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial phenotypic screen uncovers unrecognized family of extended thiourea inhibitors with copper-dependent anti-staphylococcal activity

Abstract: The continuous rise of multi-drug resistant pathogenic bacteria has become a significant challenge for the health care system. In particular, novel drugs to treat infections of methicillin-resistant Staphylococcus aureus strains (MRSA) are needed, but traditional drug discovery campaigns have largely failed to deliver clinically suitable antibiotics. More than simply new drugs, new drug discovery approaches are needed to combat bacterial resistance. The recently described phenomenon of copper-dependent inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Little work has been carried out with respect to antimicrobial effects of transition metals on human mollicutes. Previously published work with S. aureus and M. tuberculosis has demonstrated that compounds that chelate copper can exhibit antibacterial effects (Dalecki et al, 2016; Shah et al, 2016). Previous work in another laboratory during the 1980s examined the effect of Neo on Cu stress with M. gallisepticum (Smit et al, 1982; Gaisser et al, 1987b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little work has been carried out with respect to antimicrobial effects of transition metals on human mollicutes. Previously published work with S. aureus and M. tuberculosis has demonstrated that compounds that chelate copper can exhibit antibacterial effects (Dalecki et al, 2016; Shah et al, 2016). Previous work in another laboratory during the 1980s examined the effect of Neo on Cu stress with M. gallisepticum (Smit et al, 1982; Gaisser et al, 1987b).…”
Section: Discussionmentioning
confidence: 99%
“…Screening compounds for copper-dependent killing activity has resulted in the identification of new compounds with copper-dependent antimicrobial activity against Mycobacterium tuberculosis and Staphylococcus aureus (Dalecki et al, 2016; Shah et al, 2016). Previous work has been described examining the effect of antimicrobial compounds on copper-induced stress in Mycoplasma gallisepticum (Smit et al, 1982; Gaisser et al, 1987a,b; de Zwart et al, 1991), but to date studies in this area have not been conducted with human mycoplasmas or ureaplasmas.…”
Section: Introductionmentioning
confidence: 99%
“…aureus strain Newman was grown overnight in Mueller Hinton broth, used to reinoculate fresh broth, and grown to an optical density at 600nm (OD600) of ~1. Cells were washed twice in Roswell Park Memorial Institute medium (RPMI; Corning CellGrow #17105CV) and then resuspended in a mixture of RPMI plus trace elements (TE) as previously described 28 . Cells were adjusted to an OD600 of 0.004 and alamarBlue (AB; Life Technologies DAL1001) was added as a viability readout.…”
Section: Bacterial Strain Media and Growth Conditionsmentioning
confidence: 99%
“…Previously, we reported a pilot screen for CDIs against S. aureus, as well as a lead series resulting from that screen 28 . Here, we describe the continuation of that study, with two primary goals: adaptation to and deployment on an industrial high-throughput screening platform, and the identification of new and unrecognized chemical motifs associated with copper-dependent antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we described a novel approach to drug screening in which we specifically identify compounds acting in concert with copper ions, more closely mimicking in vivo conditions, as well as offering an ability to more deeply screen existing compound libraries, defraying the cost of screening studies when compared to the alternative option of synthesizing additional compounds (7-10). However, this screen, which directly compares the activities of compounds in a copper-activating medium (Cu+) against activity in a copper-deficient medium (Cu−), requires two assay plates run in parallel, and time consuming analysis to identify promising hit compounds (Figure 1).…”
Section: Introductionmentioning
confidence: 99%